The Attraction and Satisfaction of Tourists Apparalang Attractions Bulukumba Regency - A Nurul Istiana; Rosmini Maru; Ibrahim Abbas (Universitas Negeri Makassar, 2020)
This research aims to: (1) Know what is the attraction of Apparalang Bulukumba Regency, (2) know the level of satisfaction of tourists towards the attractions of the Apparalang Bulukumba Regency. This type of research is a quantitative descriptive. The research was conducted in Ara Village in the Bonto Bahari district of Bulukumba Regency. Data collection is done with observation techniques, interviews, and documentation. Data analysis uses quantitative descriptive techniques. The results showed that: (1) The attraction of Apparalang attractions includes attractions or attractions, the second the accrebility, the third amenities or facilities, and the latter a supporting factor. (2) The satisfaction of tourists here is divided into 4 indicators of the first assessment of attraction or attractions namely about tourists about the beauty of the sea, the beauty of the cliffs and photo spots can be drawn conclusions in the attraction section or attractions of the respondents are very satisfied, the second accrebilities to the attraction Apparalang satisfied with the acrebility to Apparalang, the third facilities regarding the distribution of clean water and garbage disposal they are satisfied, regarding electricity they are quite satisfied and about the counter officers they are very satisfied, the parking lot of the respondents also feel very satisfied and the latter supporting factor can be inferred also feel very satisfied.